IT Maturity Model Design and Evaluation for Sustainable Smart Cities Assessment - Adwan, Ehab Juma (Universitas Airlangga, 2025)
Background: The Economic Vision for sustainable smart cities (SSC) necessitates a continuous monitoring tool that assesses the long-term planning progress of ‎the Economic ‎maturity level (ML) which is dependent on the Maturity Models (MM) of the Enabling Technology/ICT capabilities as its analyzes, measures the maturity levels (ML) of Smart Cities (SCs), and assesses the Economic ML of the SSCs. Recent MM have several shortcomings such that they are: 1) undedicated and overlapping the SC domains, 2) missing details of SC cases, 3) applying indicators ‎from ambiguous databases, 4) unable to identify SC baseline, 5) lacking easiness, usefulness, decision support, comprehensiveness, ‎timeliness, and usage intention, and/or 6) not targeting the Economic dimension of SSC. Objective: Aiming at monitoring the long-term planning progress of ‎the SSC’s Economic ‎maturity level (ML), this study ‎‎developed and evaluated an Enterprise Architectural (EA) MM tool (BSSC-ML) that is capable to continuously assess the SC’s transition from ‎‎AS-IS (SC) to TO-BE (SSC’s Economic MLs) by ‎analyzing the Enabling Technology/ICT capabilities, 2) measuring the MLs of Enabling Technology/ICT capabilities based on 20 formulated ‎indicators, and 3) ‎assessing the MLs of Economic SSC based on 30 formulated KPIs. Methods: The Design Science ‎Research ‎methodology (DSRM) ‎orchestrated the development of BSSC-ML at which design, implementation, data collection & ‎analysis, ‎validation, ‎and evaluation were ‎‎performed by utilizing semi-structured ‎interviews were conducted ‎with 7 officials of the ‎Information & eGovernment Authority (iGA), while the ‎web content analysis and Delphi methods respectively were employed to ‎analyze the ‎official portals while preserving the validation quality and ‎‎to evaluate the model. Results: The findings revealed 50.3% ML score w.r.t 116 Business services and ‎‎3 sets of 260 Technology/ICT capabilities, 3rd ML score w.r.t Economic ‎SSC, and ‎‎‎88.123%‎ w.r.t evaluation’s acceptance rate. Conclusion: The study described the development process of BSSC-ML for SSC’ Economic MLs assessment at which the evaluation scores proved its effectiveness as a monitoring too for local and global SCs. Keywords: Technology/ICT Maturity Model, Smart City, Enterprise Architecture‎, Design and Evaluation, Economic Sustainability